The energy disruptor metformin targets mitochondrial integrity via modification of calcium flux in cancer cells - Camille Loubiere (Nature Portfolio, 2017)
Abstract Mitochondrial integrity is critical for the regulation of cellular energy and apoptosis. Metformin is an energy disruptor targeting complex I of the respiratory chain. We demonstrate that metformin induces endoplasmic reticulum (ER) stress, calcium release from the ER and subsequent uptake of calcium into the mitochondria, thus leading to mitochondrial swelling. Metformin triggers the disorganization of the cristae and inner mitochondrial membrane in several cancer cells and tumors. Mechanistically, these alterations were found to be due to calcium entry into the mitochondria, because the swelling induced by metformin was reversed by the inhibition of mitochondrial calcium uniporter (MCU). We also demonstrated that metformin inhibits the opening of mPTP and induces mitochondrial biogenesis. Altogether, the inhibition of mPTP and the increase in mitochondrial biogenesis may account for the poor pro-apoptotic effect of metformin in cancer cells.